Report on the implementation of an impact campaign for the documentary film, This Land: From cinema to community centres - a guide to developing a grassroots impact strategy - Redelinghuys, Henriette (University of Cape Town, 2021)
This Land is a forty-eight minute narrative documentary which tells the story of a small village in rural South Africa, where the community resists the development of a mine on their land. The impact campaign for This Land evolved over time, as did my role in. It could be described as a process of guided learning-in-practice, where I consulted with researchers, academics, civil society leaders and representatives from the communities where This Land was filmed. I furthermore researched other successful impact campaigns, for example the impact campaign for Miners Shot Down by Rehad Desai; I attended an impact "Boot Camp" convened by Dr. Liani Maasdorp from the Centre for Film and Media Studies at UCT; and I researched global impact case studies. While I don't describe my academic research in this report, I describe the strategy that evolved for This Land, its implementation and the relationship between the film impact goals and the impact campaign.